Disturbance observer-based Super-twisting Sliding Mode Control for Autonomous Surface Vessels - Zhang, Chang; Yu, Shuanghe; Yan, Yan (Chinese Control Conference, 2022)
This paper proposes a disturbance observer-based super-twisting sliding mode control(DOB STSMC) for trajectory tracking of the autonomous surface vessels (ASVs) subject to unknown external disturbances and modeling error. Both unknown external disturbances and system modeling error are estimated by the disturbance observer, which in turn eliminates most of the effects of the disturbance caused to the control performance. Based on this, a super-twisting sliding mode controller is designed to further suppress the residual error of disturbance compensation. The ASVs can effectively track the time-varying reference trajectory which improves the control performance of the system. In addition, the controller is continuous and chatter-free, which has greater practical value. Finally, the simulation results and comparison results highlight the superiority of the control scheme design.